GOOD CORPORATE GOVERNANCE DAN PERAN OTORITAS JASA KEUANGAN DALAM KASUS PENGGELAPAN DANA ANGGOTA KOPERASI SIMPAN PINJAM (KSP) INDOSURYA - Muhammad Irfan Dadi; Muhammad Rizal; Tetty Herawaty (LP2M Universitas Bina Bangsa, 2023)
The implementation of good corporate governance practices in cooperatives is a very important topic and is actively socialized by the Ministry of Cooperatives and SMEs. This is due to the increasing complexity of challenges in managing cooperatives in the era of globalization. Good governance practices aim to form a culture and awareness among all parties involved in the cooperative, so that its mission and social responsibility, which is to improve the welfare of members, can be realized consistently. Strengthening awareness to achieve these goals is an important key in managing a professional, trustworthy, and accountable cooperative. This study aims to investigate cases that occurred in members of the Indosurya Savings and Loans Cooperative (KSP), which caused losses of up to Rp. 106 T for its members. Therefore, it is important to provide legal certainty regarding the funds embezzled by the Indosurya Save and Loan Cooperative (KSP) and evaluate the seriousness of the government in handling this case. The descriptive method used in this study, which reveals how complex the government's approach to this case is because formally the Indosurya Savings and Loans Cooperative (KSP) is registered as a cooperative business entity under the auspices of the Ministry of Cooperatives and MSMEs. The Financial Services Authority (OJK) has the authority to revoke the cooperative's license, but is not authorized to dissolve the Savings and Loans Cooperative (KSP). The practice of moral hazard in investment activities at the Indosurya Savings and Loans Cooperative (KSP) occurs due to the weak supervision system of financial institutions, which is caused by several factors, including: (a) weaknesses in the financial supervision architecture system in Indonesia, (b) lack of information exchange and effective coordination between related institutions